Next-Generation Breeding Strategies for Climate-Ready Crops - Razzaq, Ali; Kaur, Parwinder; Akhter, Naheed; Wani, Shabir Hussain; Saleem, Fozia (Frontiers in Plant Science, 2021)
Climate change is threating the global food security by reducing crop productivity around the globe. Food security is the matter of concerns for stakeholders and policy makers as global population is predicted to bypass 10 billion in coming years. Crop improvement via modern breeding techniques along with the efficient agronomic practices, , innovations in microbiome applications and exploiting the natural variations in underutilized crops is the excellent way forward to fulfil the future food requirements. In this review we describe the next-generation breeding tools that can be used to increase the crop production by developing climate resilient superior genotypes to cope future challenges of global food security. Latest innovations in genomics-assisted breeding strategies allows to construct highly annotated crop pan-genomes to snapshot the full landscape of genetic diversity and recapture the lost gene repertoire of of a species. Pan-genomes provide new platforms to exploit these unique genes or genetic variation for optimizing breeding programs. Advent of next-generation CRISPR/Cas systems such as prime editing, base editing, de-nove domestication are revamp the genome editing for crop improvement. Also availability of versatile Cas orthologs including Cas9, Cas12, Cas13 and Cas14 improved the editing efficiency. Now, CRISPR/Cas systems has numerous application in crop research and successfully edit the major crop to develop resistant against abiotic and biotic stress. By adopting high-throughput phenotyping approaches and big data analytics tools like artificial intelligence and machine learning are heading agriculture towards automation or digitalization. The integration of speed breeding with genomics and phenomics tools can allow rapid gene identfications and ultimately accelerate crop improvement programs.. In addition, integration of next-generation multi-disciplarniry breeding platforms can open exciting avenues to develop climate-ready crops towards global food security.